Residual Oxygen Effects on the Properties of MoS2 Thin Films Deposited at Different Temperatures by Magnetron Sputtering - Peiyu Wang; Xin Wang; Fengyin Tan; Ronghua Zhang (Crystals, 2021)
Molybdenum disulfide (MoS2) thin films were deposited at different temperatures (150 °C, 225 °C, 300 °C, 375 °C, and 450 °C) on quartz glass substrates and silicon substrates using the RF magnetron sputtering method. The influence of deposition temperature on the structural, optical, electrical properties and deposition rate of the obtained thin films was investigated by X-ray diffraction (XRD), Energy Dispersive Spectrometer (EDS), Raman, absorption and transmission spectroscopies, a resistivity-measuring instrument with the four-probe method, and a step profiler. It was found that the MoS2 thin films deposited at the temperatures of 150 °C, 225 °C, and 300 °C were of polycrystalline with a (101) preferred orientation. With increasing deposition temperatures from 150 °C to 300 °C, the crystallization quality of the MoS2 thin films was improved, the Raman vibrational modes were strengthened, the deposition rate decreased, and the optical transmission and bandgap increased. When the deposition temperature increased to above 375 °C, the molecular atoms were partially combined with oxygen atoms to form MoO3 thin film, which caused significant changes in the structural, optical, and electrical properties of the obtained thin films. Therefore, it was necessary to control the deposition temperature and reduce the contamination of oxygen atoms throughout the magnetron sputtering process.